Pengembangan Video Pembelajaran Sejarah Kebudayaan Islam pada Materi Khulafaur Rasyidin Kelas VII di Pondok Pesantren Darul Hadits Kabupaten Pasaman Barat - Sopia, Nola; Supriadi, Supriadi (Lembaga Yasin AlSys, 2023)
Boarding School, West Pasaman Regency, especially in SKI subjects, seems to rarely use learning media during the learning process. This can be seen from the results of research, at the Darul Hadith Islamic Boarding School, West Pasaman Regency, it was found that so far the use of learning media is very rarely used, especially in the form of learning videos. To overcome this problem, researchers developed SKI learning video media using Khulafaur Rasyidin material. The purpose of this study was to develop valid, practical and effective video-based learning media on Khulafaur Rasyidin material in SKI class VII subjects. The research method used in this study is the Research & Development (R&D) method using the 4D version of the approach, namely Define, Design, Develop and Disseminate. The Luther Sutopo version of the multimedia development model consists of six stages, namely concept, design, material collecting, assembly, testing and distribution. The product test used is validity testing, namely content, construct and language. The practicality test by the SKI subject teacher uses the Moment Kappa formula and the effectiveness test by students uses the N-Gain formula. The results of research on SKI learning video media used by teachers and students in SKI subjects. The form of this learning media is in the form of video in mp4 format. For the product validity test it was 0.91 which was declared valid, the product practicality test result was 0.97 which was stated to be very practical and for the product effectiveness test result it was 0.80 which was stated to be very effective. So it can be concluded that the SKI learning video media on Khulafaur Rasyidin material as a learning medium is valid, practical and effective.